The Influence of the Work Environment on Work Attachment through Self-Efficacy in the Balitbang of the Indonesian Ministry of Law and Human Rights - Anggarani Winadi Prasetyoning Tyas, Ari; Nurhasanah, Nina; Sugiharto, Amo; Budin Santoso, Anton (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to determine the effect of the Work Environment on Employee Engagement, Self Efficacy on Employee Engagement, Work Environment mediated by Self Efficacy on Employee Engagement on Employee Engagement mediated by Self Efficacy. Employees as the driving force of the activities of the Republic of Indonesia Ministry of Law and Human Rights must have a good commitment to be able to produce quality human resources who are able to adjust to the community. Employee engagement can be seen from the implementation of the work he does. The analysis method used in this study is path analysis. Respondents studied were 100 respondents who were Permanent Employees at Balitbang of the Indonesian Ministry of Law and Human Rights. The results showed that there was a significant influence between the work environment variables on Self Efficacy. The direct effect between work environment variables through Self Efficacy on Employee Engagement. So, it can be said that a good Work Environment will encourage strong Self Efficacy, so that Employee Engagement can be optimized.